Problems and Challenges on Environmental Law Enforcement in Indonesia: AMDAL in the Context of Administrative Law - Ummi A'zizah Zahroh; Fatma Ulfatun Najicha (Indonesian State Law Review (ISLRev), 2022)
Environmental issues have been increasingly recognized as significant challenges facing Indonesia, as a developing country with a rapidly growing population and a rapidly expanding economy. In recent years, environmental degradation and natural resource depletion have become more acute, resulting in increased pressure on the government to take stronger action to protect the environment. Despite the existence of environmental laws in Indonesia, environmental degradation continues to occur, highlighting the need for better enforcement and stronger legal protections. One of the major environmental problems in Indonesia is deforestation, which is driven by the expansion of agricultural land, mining activities, and logging. This has resulted in significant habitat loss and biodiversity decline, as well as increased greenhouse gas emissions from the loss of forest cover. Additionally, Indonesia’s coastline and marine ecosystems are threatened by pollution from industrial activities and plastic waste, which has adverse effects on marine life and human health. Environmental laws in Indonesia include a range of regulatory measures, such as the Environmental Impact Assessment (EIA) and Forest Law Enforcement, Governance and Trade (FLEGT) programs. However, the implementation of these laws is often inadequate, with weak enforcement and a lack of effective penalties for non-compliance. Moreover, corruption and lack of political will have been identified as key factors that hinder the effective implementation of environmental laws in Indonesia.